Pulp capping materials exert an effect on the secretion of IL-1β and IL-8 by migrating human neutrophils - Bruno Neves Cavalcanti; Sigmar de Mello Rode; Cristiane Miranda França; Márcia Martins Marques (Sociedade Brasileira de Pesquisa Odontológica, 2011)
Pulp repair is a complex process whose mechanisms are not yet fully understood. The first immune cells to reach the damaged pulp are neutrophils that play an important role in releasing cytokines and in phagocytosis. The objective of this study was to analyze the effect of different pulp-capping materials on the secretion of interleukin-1 beta (IL-1β) and interleukin-8 (IL-8) by migrating human neutrophils. Neutrophils were obtained from the blood of three healthy donors. The experimental groups were calcium hydroxide [Ca(OH)2], an adhesive system (Single Bond), and mineral trioxide aggregate (MTA). Untreated cells were used as control. Transwell chambers were used in performing the assays to mimic an in vivo situation of neutrophil chemotaxis. The pulp-capping materials were placed in the lower chamber and the human neutrophils, in the upper chamber. The cells were counted and the culture medium was assayed using ELISA kits for detecting and quantifying IL-1β and IL8. The data were compared by ANOVA followed by Tukey's test (p < 0.05). The secretion of IL-8 was significantly higher in all groups in comparison to the control group (p < 0.05). The adhesive system group showed higher IL-8 than the MTA group (p < 0.05). The secretion of IL-1β was significantly greater only in the MTA group (p < 0.001). It was concluded that only MTA is able to improve the secretion of IL-1β, and all materials tested increased IL-8 secretion. These results combined with all the other biological advantages of MTA indicate that it could be considered the material of choice for dental pulp capping.